“Swamped with information”: a qualitative study of family physicians' experiences of managing and applying pandemic-related information - Young, Gillian; Mathews, Maria; Hedden, Lindsay; Lukewich, Julia; Marshall, Emily Gard; Gill, Paul; McKay, Madeleine; Ryan, Dana; Spencer, Sarah; Buote, Richard; Meredith, Leslie; Moritz, Lauren; et al. (Frontiers in Communication, 2023)
Providing family physicians (FPs) with the information they need is crucial for their participation in a coordinated pandemic or health emergency response, and to allow them to effectively run their practices. Most pandemic planning documents do not address communication plans specific to FPs. This study describes FPs' experiences and challenges with information management during the COVID-19 pandemic in Canada. We conducted semi-structured qualitative interviews with FPs across four Canadian regions and asked about their roles during different pandemic stages, as well as facilitators and barriers they experienced in performing these roles. We transcribed the interviews, used a thematic analysis approach to develop a unified coding template across the four regions, and identified recurring themes. We interviewed 68 FPs and identified two key themes specifically related to communication. The first is FPs' experiences obtaining and managing information during the COVID-19 pandemic. FPs were overwhelmed by the volume of information and had difficulty applying the information to their practices. The second is the specific attributes FPs need from the information sent to them. Participants wanted summarized and consistent information from credible sources that are relevant to primary care. Providing clear, collated, and relevant information to FPs is essential during pandemics and other health emergencies. Future pandemic plans should integrate strategies to deliver information to FPs that is tailored to primary care. Findings highlight the need for a coordinated communication strategy to effectively inform FPs in health emergencies.